HUBUNGAN OBESITAS DENGAN KEJADIAN OSTEOARTHRITIS LUTUT PADA LANSIA DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM 2020 - Justiyulfah Syah; Afif D Alba; Made Tantra Wirakesuma; Kharis Adha; Lala atika (Jurnal Rumpun Ilmu Kesehatan, 2021)
Osteoarthritis is a group of rheumatic diseases that most often causes joint disorders, causes pain and disorders in the elderly which generally attacks weight-bearing joints, especially the knee joints. Being overweight can cause damage to joint cartilage. populations with overweight or obesity have greater risk factors for knee osteoarthritis than populations with normal negative weight. excess body weight can reach four to five times greater, thereby accelerating damage to joint cartilage structures. The purpose of this study was to find out the relationship between obesity and knee osteoarthritis in the Working Area of the Batu Aji Health Center, Batam City in 2020. The type of research was analytic with a cross-sectional design, using purposive sampling by looking at secondary data. There were 67 respondents in this study. The results of this study obtained the results of the statistical test chi suare p value = 0.001 (0.05), this indicates that there is a significant relationship between obesity and the incidence of knee osteoarthritis in the elderly in the Batu Aji Health Center Work Area, Batam City in 2020. It is recommended for the elderly to can do physical activities such as gymnastics, morning walks and consume foods and drinks rich in calcium such as milk and fruits in order to maintain bone health in the elderly